A need to explore the possibilities of a controlled vocabulary / free-text indexing, in the system which facilitates the information searching activity - Kuruppu, D.C. (My University, 1998)
Information retrieval is the process of searching for i n formation and data, stored in or contained i n various formats and sources. Any system, w h i c h facilitates the information searching activity, is normally called an information retrieval system. The system is made of six major subsystems, w h i ch are the document selection subsystem, the indexing subsystem, the vocabulary subsystem, and the subsystem of usersystem interaction and the matching subsystem. The indexing subsystem consists of a bibliographic description of each document i n the collection along w i t h various access points to make this retrievable. Controlled vocabulary is considered as an important index variable and also plays a central role i n a typical retrieval system. This means that vocabulary control is a relative rather than an absolute system. Modern information retrieval systems generally make use of free-text indexing (e.g.; database on On-line system). These two indexing systemshave some artificial barrier between users and information. This paper briefly discusses the advantages and the disadvantages of controlled vocabulary and free-text indexing.
Keywords: Controlled Vocabulary, Information Searching